The Innate Immune Response to Infection Induces Erythropoietin-Dependent Replenishment of the Dendritic Cell Compartment - Einwächter, Henrik; Heiseke, Alexander; Schlitzer, Andreas; Gasteiger, Georg; Adler, Heiko; Voehringer, David; Manz, Markus G.; Ruzsics, Zsolt; Dölken, Lars; Koszinowski, Ulrich H.; Sparwasser, Tim; Reindl, Wolfgang; et al. (Frontiers in Immunology, 2020)
Dendritic cells (DC) play a key role in the adaptive immune response due to their ability to present antigens and stimulate naïve T cells. Many bacteria and viruses can efficiently target DC, resulting in impairment of their immunostimulatory function or elimination. Hence, the DC compartment requires replenishment following infection to ensure continued operational readiness of the adaptive immune system. Here, we investigated the molecular and cellular mechanisms of inflammation-induced DC generation. We found that infection with viral and bacterial pathogens as well as Toll-like receptor 9 (TLR9) ligation with CpG-oligodeoxynucleotide (CpG-ODN) expanded an erythropoietin (EPO)-dependent TER119+CD11a+ cell population in the spleen that had the capacity to differentiate into TER119+CD11chigh and TER119-CD11chigh cells both in vitro and in vivo. TER119+CD11chigh cells contributed to the conventional DC pool in the spleen and specifically increased in lymph nodes draining the site of local inflammation. Our results reveal a so far undescribed inflammatory EPO-dependent pathway of DC differentiation and establish a mechanistic link between innate immune recognition of potential immunosuppressive pathogens and the maintenance of the DC pool during and after infection.